Relationship analysis of formal and experiential learning in military survival skills using text mining - Zainol, Zuraini; Nohuddin, Puteri; Kamarudin, Nur Diyana; Siew Hoong, Angela Lee; Wani, Sharyar (2019)
Tacit knowledge tends to be an invaluable knowledge repository in lifelong learning. Critical domains such as military learning cannot solely rely on traditional manuals and methods due to the unforeseen and uncertain scenarios brought about by advances in modern warfare methods and technology. There is essential knowledge hidden in experiential learning that is very difficult to formalise but critical to be incorporated and taught. The current work aims to extract the relationships between lesson learnt from experiences and current basic military survival skills training among a group of officer cadets using the framework of document and keyword relationship analysis (FDKRA). Finally, the relationships are presented using various visualisation techniques, including word cloud, network graph and bubble graph. The research reveals the existence of important knowledge, not contained otherwise in formal documentation, and thus, highlighting the need to examine and generate a tacit knowledge corpus especially in critical domains.